The effectiveness of Kami Guibi-tang for cognitive impairment patients: A retrospective chart review - Tae-Bin Yim; Gyu-Ri Jeon; Hye-Jin Lee; Kyeong-Hwa Lee; Hye-Min Heo; Han-Gyul Lee; Seungwon Kwon; Seung-Yeon Cho; Seong-Uk Park; Woo-Sang Jung; Sang-Kwan Moon; Chang-Nam Ko; et al. (Heliyon, 2024)
Background: and Purpose: The number of patients with cognitive impairment is increasing worldwide. Therapeutic drugs that slow disease progression are being developed; however, further research is required. This study investigated the effects of Kami Guibi-tang on patients with various types of cognitive decline. Methods: This study was a single-center, retrospective chart review of patients who visited KyungHee University Hospital at Gangdong from January 2015 to March 2022. The study included participants who took Kami Guibi-tang for more than 90 days and were assessed on the Korean version Mini-Mental State Examination (MMSE-K) scores before and after treatment. Participants who received other liquid herbal medicines during the treatment were excluded. The outcome of interest was changed scores in MMSE-K and Short form of Geriatric Depression Scale (S-GDS). Results: A total of 31 participants were included. The total MMSE-K score significantly increased with time and showed a significant increase at 3 and 9 months compared with baseline. Among the MMSE-K subscores, the orientation subscore showed a significant increase at three months compared with baseline, and the attention and calculation subscore showed a significant increase with time. In addition, four participants with vascular dementia showed a significant increase in the total MMSE-K score over time and a significant increase after 9 months compared with baseline. The S-GDS score in 31 participants showed a significant decrease with time and at all time points compared with baseline. Conclusions: Kami Guibi-tang may improve cognitive function in patients with cognitive decline.